Evaluate and Develop Innovative Pavement Repair and Patching: Taconite-Based Repair Options - Zanko, Lawrence M.; Hopstock, David M.; DeRocher, Will (Minnesota Department of Transportation, 2016)
In support of a broader MnDOT effort to evaluate current practices, materials, and policies for pavement patching and repair for both asphalt and concrete pavements, the University of Minnesota Duluth Natural Resources Research Institute (NRRI) conducted additional evaluation, refinement, field testing, and performance monitoring of two taconite-related approaches to pavement repair that rely on mixes/techniques that contain (or are enhanced by) taconite mining byproducts and co-products. The first taconite-related approach to pavement repair uses a rigid pavement/pothole repair compound formulation developed and patented by NRRI that is fast-setting, taconite-based, and contains no petroleum or Portland cement. Depending on the formulation, the repair compound can be water-activated or activated by a chemical solution. A water-activated formulation referred to as Rapid Patch was the focus of the investigation. The second taconite- related approach to pavement repair employs a high-power (50kW), vehicle-based (truck-mounted) microwave system for in-place pothole/pavement repair/recycling in which magnetite and/or magnetite-containing aggregate (taconite rock) can enhance microwave absorption and therefore the system’s performance. The two repair alternatives evaluated during this project merit further development and consideration, as the field performance of both suggests they have long-term potential for more widespread use. Based on feedback from maintenance personnel who used and/or observed both repair alternatives during the project, both alternatives would benefit from operational modifications that would reduce the deployment time required to complete a repair and increase the number of repairs that can be accomplished during a single shift. Doing so would likely lead to greater acceptance and more widespread use.
Keywords: Paving; Pavement maintenance; Patching; Taconite; Microwave devices; Technological innovations